Analyzing Guest Satisfaction and Dissatisfaction of Hotels in Dakar: Insights from User-Generated Reviews - CARVALHO , Ginette B. F. (Revue Internationale des Sciences de Gestion, 2024)
The tourism and hospitality industry is increasingly relying on user-generated content (UGC) to gauge customer satisfaction and dissatisfaction. However, very few studies have leveraged this valuable source of data to analyze guest experiences at hotels in the context of Sub-Saharan African markets. This study aims to address this gap by identifying the key determinants of satisfaction and dissatisfaction among hotel visitors in Dakar, Senegal. To explore hotel customer experiences, we examined user reviews posted on Booking.com (1,103 positive reviews and 813 negative reviews) by guests who stayed at one of 14 prominent hotels located in the Dakar, using convenience sampling, a non-probabilistic sampling method. Building on Kano’s three-factor theory of customer satisfaction, we identified key service attributes that drive both satisfaction and dissatisfaction based on guest feedback. The findings of this study contribute to the advancement of research in this domain while also offering valuable insights that can guide hotel managers in improving service management and enhancing the overall customer experience.